Genetic Variation - Trindade Maia, Rafael; de Araújo Campos, Magnólia (IntechOpen, 2021)
Genetic diversity is one of the measures of biodiversity and has consequences in biological variation. It is crucial to understand the evolutionary and adaptative processes in all living species. This book is an interdisciplinary and integrated work that will contribute to the knowledge of academics from different areas of biological sciences. This collection of scientific papers was chosen and analyzed to offer readers a broad and integrated view of the importance of genetic diversity in the evolution and adaptation of living beings, as well as practical applications of the information needed to analyze this diversity in different organisms. This book was edited by geneticist researchers and provides academics with up-to-date and quality information on the subject.